Fiber Optic Vibration Sensor Based on the Tilted Fiber Bragg Grating - Jiali An; Tao Liu; Yongxing Jin (Advances in Materials Science and Engineering)
A temperature-insensitive fiber optic vibration sensor based on the tilted fiber Bragg grating (TFBG) is presented. The sensing head is formed by insertion of a small section of MMF between a single-mode fiber and the TFBG. The reflection light from this tilted fiber Bragg grating includes two parts: the reflected Bragg mode and the cladding modes. The cladding modes were coupled back into the core mode as a function of the multimode fiber. The power of the cladding modes is sensitive to vibration, so the external vibration measurement can be obtained through the cladding mode average output power. Experiment results show that the root mean square (RMS) of the detection error of the average power was 0.01 μW within the temperature range from 20 to 70°C, so it is proved to be temperature independent; its frequency response has been tested to 1 KHz.